The Impact of Phase Change Materials on Electricity Consumption in Prefabricated Temporary Houses - Fatih Selim Bayraktar; Ramazan Köse (Energy Science & Engineering)
ABSTRACT Following disasters, sheltering displaced populations becomes an immediate and critical concern. Prefabricated temporary housing (PTH) is a widely adopted solution due to its rapid deployment, ease of transportation, and swift assembly. However, their lightweight construction presents a significant drawback in terms of thermal performance. This limitation arises from the inherently low thermal inertia of PTHs, hindering their ability to regulate heat transfer and maintain thermal comfort for occupants. This study investigates the potential of incorporating phase change materials (PCMs) into the inner surfaces of PTHs to improve their thermal inertia and thermal mass properties. By leveraging the latent heat storage capacity of PCMs, the objective is to reduce the reliance on electrical heating/cooling systems, thereby minimizing energy consumption. The effectiveness of PCM integration was evaluated over a 1‐month period under winter climate conditions, with electricity consumption serving as the primary metric. According to the results, the incorporation of PCMs led to a reduction in average electricity consumption by 16%, weighted average electricity consumption by 16.2%, and cumulative electricity consumption by 16.6%, achieving significant energy savings.